Dominant cardiovascular diseases treated by traditional Chinese medicine: Clinical evidence and distinctive therapeutic characteristics - Jie Wang; Jun Hu; Yongmei Liu; Zhilin Jiang; Jiawen Cheng; Cong Chen; Chao Liu; Lanchun Liu (Science of Traditional Chinese Medicine)
Abstract. Traditional Chinese medicine (TCM) with a long history in China has demonstrated unique advantages in treating a variety of cardiovascular diseases, with promising prospects. We exemplify the TCM advantages with 3 major cardiovascular diseases: coronary heart disease, hypertension, and chronic heart failure. With both national and international guidelines, consensus, systematic reviews, and randomized controlled trials as evidence, we used the modified Jadad and AMSTAR-1 scales to evaluate the evidence quality and then systematically evaluated the clinical effects and benefits of TCM on cardiovascular diseases, aiming to provide fresh insights into the research methodologies and future development directions for TCM-dominant diseases.